An Act for the Regulation of the Militia of the Commonwealth of Pennsylvania (20 March, 1780), § 57, Penalty on Officers Misbehaving while on Parade; § 60, Rules and regulations, 12th rule. - (:unkn) unknown (My University, 1780)
§ 57 "...and if any non-commissioned officer or private shall, on any occasion of parading the company to which he belongs, appear with his arms and accoutrements in an unfit condition, or be found drunk or shall disobey orders or use any reproachful or abusive language to his officers or any of them ; or shall quarrel himself, or promote any quarrel among his fellow soldiers, he shall be disarmed and put under guard, by order of the commanding officer present, until the company is dismissed, and shall be fined in any sum not exceeding the price of ten day's [sic] labour, nor less than one day's labour.
Keywords: ARMED FORCES